Integrated microbiology and metabolomics analysis reveal the fermentation process and the flavor development in cigar tobacco leaf - Guanghai Zhang; Yue He; Wanlong Yang; Ziyi Liu; Zhonglong Lin; Tikun Zhang; Xiaohui He; Huachan Xia; Mengting Huo; Heng Yao; Gaokun Zhao; Yuping Wu; et al. (Microbiology Spectrum)
ABSTRACT The purpose of this study was to elucidate how the microbiota affects the metabolic state and characteristic flavor development of cigar tobacco leaves (CTL) in the fermentation process through microbial metabolism and co-metabolism with the host. The results showed that core bacterial communities in the fermentation process were Cyanobacteria, Pseudomonas, and Staphylococcus, and Aspergillus, Penicillium, and Inocybe were the most metabolically active fungi. Pseudomonas fulva, Staphylococcus nepalensis, Bacillus subtilis, Stenotrophomonas rhizophila, Alternaria alternata, and Aspergillus cristatus could degrade carbon and nitrogen compounds, such as protein, starch, lignin, and nicotine. There were 12 common non-volatile metabolites and three common volatile metabolites in DH, LC, PE, and YX before and after fermentation, of which menatetrenone, solanidine, γ-glutamylphenylalanine, carotol, and phenol, 4-(1,1,3,3-tetramethylbutyl) were significantly different before and after fermentation. The synthesis and degradation metabolism of various amino acids, alkaloids, and flavonoids are the key metabolic pathways of characteristic flavor development during CTL fermentation. Co-occurrence and interaction patterns showed that seven bacteria and 12 fungi were strictly linearly positively or negatively correlated with 72 and 55 volatile compounds, respectively. In conclusion, this study preliminarily confirmed that CTL fermentation is a microbially mediated carbon–nitrogen coupling metabolism. The carbohydrates in tobacco leaves were largely decomposed and consumed, providing energy sources for microorganisms and the carbon skeleton required for cell construction. The nitrogen-containing macromolecular compounds were degraded to form volatile compounds or flavor precursors with typical flavor.IMPORTANCEThe development of the metabolic state and characteristic flavor of cigar tobacco during fermentation is the key to process control. Innovative discoveries in the development of the metabolic state and characteristic flavor of cigar tobacco during fermentation are the key to process control. Innovative discoveries of core functional microorganisms and key metabolites were made during fermentation, suggesting potential pathways for carbon and nitrogen metabolisms. We demonstrate for the first time that cigar tobacco leaf fermentation is a microbially mediated carbon–nitrogen coupling metabolism. Many carbohydrates in tobacco leaves are decomposed and consumed to provide energy source and carbon skeleton for the construction of microbial cells, and nitrogen-containing macromolecular compounds are degraded to form volatile compounds or flavor precursors with typical flavors.